1989
DOI: 10.1093/nar/17.13.4937
|View full text |Cite
|
Sign up to set email alerts
|

Direct solid phase sequencing of genomic and plasmid DNA using magnetic beads as solid support

Abstract: Approaches to direct solid phase sequencing of genomic and plasmid DNA have been developed using magnetic beads, coated with streptavidin, as solid support. The DNA is immobilized through selective incorporation of biotin into one of the strands. A single stranded template, suitable for sequencing, is obtained through strand-specific elution. Using this concept, in vitro amplified plasmid DNA and chromosomal DNA were sequenced directly from single colonies. The solid phase approach ensures that the amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
335
0
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 716 publications
(338 citation statements)
references
References 18 publications
2
335
0
1
Order By: Relevance
“…Capturing of the amplified DNA on a solid support comprises a simple and efficient single-step purification of the DNA from the PCR mixture. Solid phase techniques are applicable to automatic sequencing procedures, as shown recently by Hultman et al and Voss et al [19,20]. We conclude that nucleotide sequencing of affinity-captured PCR-amplified DNA fragments is a promising approach to the routine diagnosis of genetic disorders.…”
Section: Conclusion and Prospectssupporting
confidence: 59%
“…Capturing of the amplified DNA on a solid support comprises a simple and efficient single-step purification of the DNA from the PCR mixture. Solid phase techniques are applicable to automatic sequencing procedures, as shown recently by Hultman et al and Voss et al [19,20]. We conclude that nucleotide sequencing of affinity-captured PCR-amplified DNA fragments is a promising approach to the routine diagnosis of genetic disorders.…”
Section: Conclusion and Prospectssupporting
confidence: 59%
“…1, indicated that the patient had no apparent deletion in her Y chromosome ( Table 2). The PCR coupled with the direct solid phase sequencing of the conserved region of SRY with magnetic beads as solid support [7] revealed that her SRY gene had a 100% nude- otide sequence identity with the reported cloned sequence [1].…”
Section: Case Reportmentioning
confidence: 96%
“…The biotinylated amplicons were immobilized onto streptavidin-coated solid support and strand speci®c elution with 0.05 M NaOH produced a clean template for sequencing. Solid-phase sequencing was performed as published (Berg et al, 1995;Hultman et al, 1989) with automated laser¯uorescent analysis (ALF TM , Pharmacia Biotech AB, Uppsala, Sweden). The sequences were compared with wild type p53 sequence as exempli®ed in Figure 4.…”
Section: Solid-phase Sequencingmentioning
confidence: 99%